A comparative study of misoprostol versus surgical management of incomplete and missed miscarriage - Verma, Monica; Thakur, Vibhuti; Awasiya, Pratibha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The aim of this study is to assess the effectiveness and acceptability of using vaginal Misoprostol for management of spontaneous incomplete and missed miscarriage as an alternative to direct vaginal surgical evacuation in our setting and also to compare the efficacy and patient satisfaction of the medical method with surgical method in same. Methods: this is a prospective comparative study performed on randomly divided 200 patients in two groups. Each group of patients are case of missed or incomplete abortion in first trimester.(5-12 weeks). Group one received Misoprostol tablet 600 mcg single dose per vaginally, and second group underwent surgical vaginal evacuation directly under local anesthesia (para-cervical block . both groups were compared in terms of success, complications, pain and patient satisfaction. Results: 97% success rates were obtained in the medical treatment group. Surgical group had 95% success rates. 3 patients underwent repeat surgical evacuation in the medical group. Bleeding was more and prolonged in the patients managed by Misoprostol, 27% patients had moderate bleeding. Though bleeding was less in the surgical group but there was excruciating pain and weakness as the procedure being done under local anesthesia, 98% patients experienced pain in surgical group. Satisfaction rates in the misoprostol group were 100%. Conclusions: Misoprostol is effective in complete evacuation of uterus in incomplete and missed miscarriage. Patients are highly satisfied with the misoprostol treatment as they didn’t have to get hospitalized. The bleeding was more or less like menstrual bleeding which did not affect the daily chores of the women. It is as effective as surgical evacuation and patient satisfaction is much more than the surgical evacuation.